2003
DOI: 10.1042/cs20020263
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like receptor 4 is associated with enteroviral replication in human myocarditis

Abstract: Previous studies have demonstrated that inflammatory cytokine expression associated with enteroviral (EV) infection may play an important role in human myocarditis. However, the mechanism of the host immune response against viral pathogens has not been fully understood. The aim of the present study was to determine whether Toll-like receptor 4 (TLR4) and EV RNA are present in human myocarditis. Endomyocardial biopsy samples were obtained from 44 patients with myocarditis and five controls. Levels of plus- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 21 publications
(34 reference statements)
2
37
0
3
Order By: Relevance
“…23 Our previous study has shown that increased expression of TLR4 is associated with EV replication in human myocarditis. 24 These reports suggest that activation of TLR4 may play an important role in host immune response against viral infection. In the present study, high levels of TLR4 mRNA expression were seen in DCM patients positive for both plus-and minus-strand EV RNA.…”
Section: Discussionmentioning
confidence: 99%
“…23 Our previous study has shown that increased expression of TLR4 is associated with EV replication in human myocarditis. 24 These reports suggest that activation of TLR4 may play an important role in host immune response against viral infection. In the present study, high levels of TLR4 mRNA expression were seen in DCM patients positive for both plus-and minus-strand EV RNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, because cardiac myocytes also express TLR4, LPS could directly alter myocyte function. Studies have shown that myocyte TLR4 is functional in failing myocardium, 13 myocarditis, where TLR4 correlates to enteroviral replication and cardiac dysfunction, 14 and cytokine production within the heart of endotoxemic mice. 15 Interestingly, none of these studies has addressed which TLR4-positive cell types are responsible for the observed cardiac dysfunction.…”
mentioning
confidence: 99%
“…Our experimental findings strongly support a role for TLR2 as an initiator of cardiomyocyte hypertrophy triggered in response to T. cruzi as well as downstream events such as NF-B activation and IL-1␤ production. While cardiomyocytes are not normally associated with a role in host defense, accruing evidence indicates that these cells participate in cardiac surveillance, responding rapidly to endogenous indicators of stress through the activation of intrinsic Toll-like receptors (11,12,38). Our results highlight the potential for intrinsic cardiomyocyte TLRs to play a role in initiating a hypertrophic response following exposure to pathogens, pathogen products, or endogenous signals emanating from damaged cardiac muscle (11,12,38).…”
Section: Discussionmentioning
confidence: 74%
“…While cardiomyocytes are not normally associated with a role in host defense, accruing evidence indicates that these cells participate in cardiac surveillance, responding rapidly to endogenous indicators of stress through the activation of intrinsic Toll-like receptors (11,12,38). Our results highlight the potential for intrinsic cardiomyocyte TLRs to play a role in initiating a hypertrophic response following exposure to pathogens, pathogen products, or endogenous signals emanating from damaged cardiac muscle (11,12,38). The rapid onset of hypertrophy observed in cultured myocytes, within 24 to 48 h, suggests that physiologic changes in cardiomyocytes initiated by engagement of intrinsic TLRs in the heart, either locally or globally, may precede an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%